KINERJA KEUANGAN DAERAH MEMODERASI PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM PADA PERTUMBUHAN EKONOMI - Pratama Putra, Agus Adi; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2017)
Increased PAD and DAU allegedly not necessarily be increasing economic growth due to factor contingencies, namely the Regional Financial Performance. This study aims to determine the effect of PAD and DAU on Economic Growth and the ability of the Regional Financial Performance moderating PAD and DAU on economic growth. This study covers 8 districts and 1 municipality in the province of Bali. The data used is APBD realization and PDRB from years 2009 to 2013. The data in this study has been qualified classical assumption test and conformance test were processed using techniques Moderated Regression Analysis (MRA). Based on the results that has been done shows that PAD has a positive effect but not significant on economic growth while DAU has no effect on economic growth. Moderation test shows that the Regional Financial Performance able to increase PAD influence on economic growth, while the Regional financial performance as the moderating is not able to increase DAU effect on economic growth in the province of Bali.
Keywords: PAD, DAU, Economic Growth, Regional Financial Performance